De novo methicillin-resistant Staphylococcus aureus vs. methicillin-sensitive Staphylococcus aureus infections of the spine, similar clinical outcome, despite more severe presentation in surgical patients - Ishak, Basem; Abdul-Jabbar, Amir; Moss, Gregory B.; Yilmaz, Emre; von Glinski, Alexander; Frieler, Sven; Unterberg, Andreas; Blecher, Ronan; Altafulla, Juan; Roh, Jeffrey; Hart, Robert A.; Oskouian, Rod J.; et al. (Neurosurgical review, 2021)
Vertebral osteomyelitis (VO) is a severe infection of the vertebral body and the adjacent disc space, where Staphylococcus aureus is most commonly isolated. The objective of this retrospective study was to determine risk factors for and compare outcome differences between de novo methicillin-resistant Staphylococcus aureus (MRSA) VO and methicillin-sensitive Staphylococcus aureus (MSSA) VO. A retrospective cohort study was performed by review of the electronic medical records of 4541 consecutive spine surgery patients. Among these 37 underwent surgical treatment of de novo MRSA and MSSA spinal infections. Patient demographics, pre- and postoperative neurological status (ASIA impairment score), surgical treatment, inflammatory laboratory values, nutritional status, comorbidities, antibiotics, hospital stay, ICU stay, reoperation, readmission, and complications were collected. A minimum follow-up (FU) of 12 months was required. Among the 37 patients with de novo VO, 19 were MRSA and 18 were MSSA. Mean age was 52.4 and 52.9 years in the MRSA and MSSA groups, respectively. Neurological deficits were found in 53% of patients with MRSA infection and in 17% of the patients with MSSA infection, which was statistically significant (p < 0.05). Chronic renal insufficiency and malnutrition were found to be significant risk factors for MRSA VO. Preoperative albumin was significantly lower in the MRSA group (p < 0.05). Patients suffering from spinal infection with chronic renal insufficiency and malnutrition should be watched more carefully for MRSA. The MRSA group did not show a significant difference with regard to final clinical outcome despite more severe presentation.